FENOMENOLOGI PENDIDIKAN DAN TRANSFORMASI KESADARAN BERPIKIR MATEMATIS MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Fitriani, Fitriani; Zen, Zelhendri; Jasrial, Jasrial (STKIP Pesisir Selatan, 2025)
This study explores the transformation of mathematical thinking awareness among mathematics education students through a phenomenological lens. Thirty undergraduate students in the Mathematics Education Study Program at Universitas Muhammadiyah Tapanuli Selatan participated as research subjects selected through purposive sampling. Data were obtained through semi-structured interviews, participatory observations, and reflective documentation, and analyzed using Colaizzi’s descriptive phenomenological method. The findings demonstrate a three-stage transformation of awareness: epistemic, metacognitive, and ontological. Epistemically, students shifted from memorizing formulas toward conceptual understanding driven by meaningful learning needs. Metacognitively, errors, reflective dialogue, and self-explanation triggered deeper strategic awareness, revealing the role of regulation and emotional control in sustaining understanding. Ontologically, mathematics became integrated into students’ self-identity as future educators, shaping how they perceive learning as part of lifelong intellectual and personal development. Taken together, students no longer view mathematics merely as procedural knowledge but as a way of thinking that guides interpretation, reasoning, and awareness of learning processes.